Breakthrough Pain Management in Patients Undergoing Radiotherapy: A National Survey on Behalf of the Palliative and Supportive Care Study Group. Issue 6 (November 2015) - Caravatta, Luciana; Ramella, Sara; Melano, Antonella; Trippa, Fabio; Santacaterina, Anna; Bacchiddu, Simonetta; Mandoliti, Giovanni; Mantini, Giovanna
Aims: To assess the contribution of radiation oncologists in Italy in current management of breakthrough pain (BtP). Methods: In 2012, the Palliative and Supportive Care Study Group of the Italian Association of Radiation Oncology (AIRO) proposed a survey. All Italian radiation oncologists were individually invited to complete an online questionnaire regarding their management of BtP in patients undergoing radiotherapy treatment. Results: A total of 303 Italian radiation oncologists (of 330 who had access to the Web site) completed the questionnaire over an 8-month period. Some important differences were shown in pain intensity assessment by validated measurement scales, as well as in setting and prescribing analgesic therapy to prevent procedural pain. These differences were also reviewed and discussed related to international guidelines and data available from the literature. Conclusions: Compared to other medical professionals, the involvement of radiation oncologists in cancer pain management remains marginal, at least in Italy. More than 70% of radiation oncologists directly optimized the analgesic therapy during the treatment course and more than 50% implemented specific treatment for BtP. However, the ability of the radiation oncologist to manage BtP could be improved. In order to increase the consciousness of systematic symptom measurement and to spread the knowledge of the best type of analgesic drugs to be used, training events promoted by national associations, such as AIRO, and a collaborative multidisciplinary approach of the management of cancer pain will be promoted.